Analysis of Language Materials and Their Presentation in Arabic Language Textbooks - Mahyudin Ritonga; Hanomi Hanomi; Ellia Roza (Program Pascasarjana UMSB, 2023)
In the learning process, of course, we need textbooks, where textbooks or teaching materials are the most important factor among the factors in the running of the learning process in all fields of education, especially in Arabic language learning. At present, Arabic teaching materials in the form of textbooks used at various levels of education are in fact undeveloped, while academic demands are related to the need for renewal and development related to Arabic teaching materials. The material raised in the textbook must also be complete and the presentation method must also be interesting in accordance with the demands of learning. The purpose of this study is to provide an overview and analysis related to linguistic material and presentation methods in Arabic textbooks. The research used is library research with a qualitative approach. Data collection techniques in this study used documentation techniques, where the data collected by the author from various primary and secondary sources in the form of textbooks and journals. This research produces some Arabic language materials and methods of presentation in textbooks and methods that can be used by teachers during the Arabic language learning process.